2013
DOI: 10.1002/bab.1066
|View full text |Cite
|
Sign up to set email alerts
|

Trimeric lN‐carbamoylase from newly isolated Brevibacillus reuszeriHSN1: A potential biocatalyst for production of l‐α‐amino acids

Abstract: l-N-carbamoylase was isolated from Brevibacillus reuszeri HSN1 and purified to homogeneity in three steps, which is a reasonably short protocol for native l-N-carbamoylase. The enzyme purification protocol resulted in ≈60-fold purification of l-N-carbamoylase with specific activity of 145 µmol/Min/mg. The subunit and native molecular mass were found to be 44.3 and 132 kDa, respectively. Temperature and pH optima were determined as 50°C and 8.5, respectively. The enzyme had retained ≈86% activity at 50°C when i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The protein was analysed as purified and following elution from a desalting column to remove any loosely bound metals. Raw detected values for 55 Mn, 59 Co, 60 Ni, 63 Cu, 66 Zn and 111 Cd were compared with commercial standard curve preparations (Merck). 107 Ag and 115 In were used as internal standards.…”
Section: Inductively Coupled Plasma Mass Spectrometry Analysismentioning
confidence: 99%
“…The protein was analysed as purified and following elution from a desalting column to remove any loosely bound metals. Raw detected values for 55 Mn, 59 Co, 60 Ni, 63 Cu, 66 Zn and 111 Cd were compared with commercial standard curve preparations (Merck). 107 Ag and 115 In were used as internal standards.…”
Section: Inductively Coupled Plasma Mass Spectrometry Analysismentioning
confidence: 99%
“…Many species of Brevibacillus have been considered biological resources for the production of various enzymes, especially cyclodextrin glycosyltransferase used in cosmetics, pharmaceutical, and food industries, serine proteases, biomaterials caused improvement of plants growth or nodulation of roots, antimicrobial peptides, insecticidal agents, extracellular polysaccharide substances (EPSs), polyhydroxyalkanoate copolymers, L-amino acids, etc. [188][189][190][191]. Additionally, Brevibacillus brevis strains can degrade many organic compounds such as triphenyltin, pyrene, triphenyl phosphate, or textile dyes, and their high resistance to heavy metals makes them the right choice to use in contaminated sites [192][193][194][195].…”
Section: Paenibacillaceae Generamentioning
confidence: 99%
“…Several studies have reported the ability of B. reuszeri bacteria, including capable of producing extracellular metalloprotease/thermolysin inhibitors (Kobayashi et al 2004) to produce L-methionine-N-carbamoylase as potential biocatalyst for L-amino acid production (Nandanwar et al 2013), phosphate dilution, plant growthpromoting rhizobacteria (PGPR) (Pradesh et al 2019;Prasad et al 2019;Yildirim et al 2011), and antimicrobial bioactive compound production (Gholizadeh et al 2013;Yang and Yousef 2018).…”
Section: Brevibacillus Reuszerimentioning
confidence: 99%